A review of application of natural products as fungicides for chili - Ngibad, Khoirul; Muadifah, Afidatul; Jannah Triarini, Lailatul; Rizki Amalia, Laily; Karel Damayanti, Novita (Environmental and Toxicology Management, 2021)
Anthracnose disease in chillies is a serious problem for farmers. So far, synthetic fungicides have been used as solution for the treatment of this disease. However, the side effects of synthetic fungicides to  public health and environment raised awareness on  alternative fungicides derived from natural resources. This paper aims to review plants that  are  potential as an alternative to fungicides for chili plantation, fabrication of test solutions, in vitro and in vivo fungicide test. Many plants  were investigated as alternatives to plant-based fungicide. The utilization of leaves as samples including rhizomes, roots, tubers, weevils, seeds, fruit, flowers and  other parts of the plant. The extract fabrication method used as a fungicide test include: maceration method, gradual fractionation method, and decoction method. The maceration method is the method most widely used to extract fungicidal active compounds from plants. Some studies that carried out in vitro tests were unable to compare with synthetic fungicides so it was not possible to determine their effectiveness for plant-based fungicide for chillies when compared to synthetic fungicides. In vitro Extract of 80% alcohol and 10%/60% n-hexane of pacar cina (Aglaia odorata L.) leaves can be compared with the performance of propineb 0.2%. In addition, the 60% and 70% kirinyuh (Chromolaena odorata L.) leaf extracts were also able to match Acrobat 0.2% performance in vitro. Based on the in vivo test, suren (Toona sureni Merr) leaf extract and nut bulbs can be used as an alternative to vegetable / natural fungicides to help overcome the problem of anthracnose in chilies.